Principles of the Guidance of Exploration for Orientation and Specification of Action - van Andel, Steven; McGuckian, Thomas B.; Chalkley, Daniel; Cole, Michael H.; Pepping, Gert-Jan (Frontiers in Behavioral Neuroscience, 2019)
To control movement of any type, the neural system requires perceptual information to distinguish what actions are possible in any given environment. The behavior aimed at collecting this information, termed “exploration”, is vital for successful movement control. Currently, the main function of exploration is understood in the context of specifying the requirements of the task at hand. To accommodate for agency and action-selection, we propose that this understanding needs to be supplemented with a function of exploration that logically precedes the specification of action requirements with the purpose of discovery of possibilities for action—action orientation. This study aimed to provide evidence for the delineation of exploration for action orientation and exploration for action specification using the principles from “General Tau Theory.” Sixteen male participants volunteered and performed a laboratory-based exploration task. The visual scenes of different task-specific situations were projected on five monitors surrounding the participant. At a predetermined time, the participant received a simulated ball and was asked to respond by indicating where they would next play the ball. Head movements were recorded using inertial sensors as a measure of exploratory activity. It was shown that movement guidance characteristics varied between different head turns as participants moved from exploration for orientation to exploration for action specification. The first head turn in the trial, used for action-orientation, showed later peaks in the velocity profile and harder closure of the movement gap (gap between the start and end of the head-movement) in comparison to the later head turns. However, no differences were found between the first and the final head turn, which we hypothesized are used mainly for action orientation and specification respectively. These results are in support of differences in the function and control of head movement for discovery of opportunities for action (orientation) vs. head movement for specification of task requirements. Both are important for natural movement, yet in experimental settings,orientation is often neglected. Including both orientation and action specification in an experimental design should maximize generalizability of an experiment to natural behavior. Future studies are required to study the neural bases of movement guidance in order to better understand exploration in anticipation of movement.